When solidarity and misery meet in the shadow of a massacre: Moral values reflected in the novel ‘Human Acts’ - Audi Yundayani; Benedicta Lintang Larassaty; Bejo Sutrisno (EduLite: Journal of English Education, Literature and Culture, 2021)
The crisis that the world is in today has brought people together through the suffering they share. It leads to the presence of solidarity, which shows how people come hand in hand to help each other, showing that humanity exists even in difficult times. This paper seeks to analyze the portrayal of solidarity and suffering as part of the moral values of Han Kang's novel 'Human Acts,' which deals with the similar crisis that occurred in South Korea in 1980, known as the Gwangju Uprising. It applies descriptive qualitative research which concentrates directly and clearly on the aspects in the novel. It is learned that the characters in the novel convey the moral values most through the way in which they respect and care for one another and that the suffering shared between the characters is part of both their loss and their survival because of the solidarity they have built along the way. The moral values depicted in the novel ‘Human Acts’ are not merely fiction. It was realistically shown during the Gwangju Uprising and is now being shown in the current situation of the pandemic.